If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 = -3 + 14 Reorder the terms: 3 + 6x = -3 + 14 Combine like terms: -3 + 14 = 11 3 + 6x = 11 Solving 3 + 6x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6x = 11 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = 11 + -3 6x = 11 + -3 Combine like terms: 11 + -3 = 8 6x = 8 Divide each side by '6'. x = 1.333333333 Simplifying x = 1.333333333
| 14-(6x-5)=5(2x-1)-4 | | P=5sfora | | 8d+0=0 | | 3f-2=13 | | p-20=39 | | y-2y-5=0 | | 14x+14=162 | | In(x+3)+lnx=1 | | 14x+14=176 | | 3x-6y-15=0 | | 4/9x72 | | 9.5p-9.3=-39.4+5.2p | | 5x-2x-16= | | 3y-9+y+25=5y+20-3y | | 8+2r-3=8r+21-4r | | 3x-40=50x+8 | | 2X+Y=216 | | 5x+3y=543 | | 30x-3x^2=0 | | 5x+3(2x-7)=ax+b | | 13X+13X^2=9 | | 6z-17=-17+z | | 8-7x=68-28 | | 6x+8y=1/10 | | 4x+14=42-10x | | x+(1/5)x=30 | | -24-3x=13-9x | | 8(7)-3(-2)=3 | | 8(7)-33(-2)=3 | | 30-.20= | | 2(r-.02)=1.5r | | 5lnx=-3 |